The Impact of Information Provision on the Social Acceptance of Shale Gas Development: A Review-Based Inclusive Model - Kânoğlu, Dilge G.; Soytaş, Uğur (Frontiers in Energy Research, 2018)
Social acceptance is critical to the market penetration of new products and technologies as well as the successful implementation of policies, including those concerning energy demand. The hydraulic fracturing technique employed in the development of shale gas has been followed by controversy and this has resulted in the emergence of heterogeneity in attitudes towards the process. This review-based perspective surveys selected contributions of psychology to the literature on social acceptance. While not comprehensive, it aims to identify the factors that determine the acceptance of shale gas development. The proposed model for understanding acceptance encompasses the factors: perceived benefits, risks and costs, procedural and distributional fairness, trust, outcome efficacy, problem perception, knowledge and experience. The study then discusses adequate means of modulating distinguished responses to the same impulse and proposes information provision as an effective methodology. This has become a viable option because survey data and numerous opinion polls have underlined the deficiency of knowledge and the lack of a clear understanding of the risks associated with and benefits to be derived from shale gas development. Moreover, unlike experience, that is much more difficult to regulate, knowledge provides us with three channels namely the source, content and means of communication that allow for spatial divergences in policymaking.